Rules and Regulations for the Investment Account. (Policy Papers; Policy Paper, 2019)
Rules and Regulations for the Investment Account, which were adopted on January 23, 2013 and amended thereafter, were further amended on May 13, 2019 by the Executive Board of the IMF.